Caracterização do bio-óleo produzido por pirólise rápida do bagaço de cana-de-açúcar - Silva, Cleuzilene Vieira da (2013)
In the present work, the process of thermal decomposition of bagasse Cane Sugar (BCA) was used to understand the behavior of the raw material for the production of bio-oil (BO) from Fast Pyrolysis process. The study was objectified on two fronts: i) characterization of the BCA and ii) Characterization of BO. BCA was characterized by elemental analysis and has the chemical composition according to the formula CH1,48O0,71N0,0054 The test results shown BCA shown that this is an important potential source lignocellulose for the production of BO, since this has a low ash content (3.7%) and high content of volatile materials (81.8%), moreover, the calorific value of the BCA was 15.9 MJ/kg, a value close to that obtained with other lignocellulosic sources. The thermal decomposition of BCA was assessed through thermogravimetric curves in inert atmosphere and in synthetic air. The curves show that the presence of oxygen has an influence on the final products of decomposition and the values of activation energy (Ea) for the process. The kinetic study was performed using the methods isoconversionais Ozawa-Flynn-Wall (OFW) and Vyazovkin (V). The present study aimed to contribute information about the kinetics of thermal decomposition of BCA in the presence of oxygen, considering the process on a pilot scale, held oxidative pyrolysis with atmospheric air, becoming self-sufficient through the release of energy by combustion Part of biomass for energy production. For the decomposition reaction conversions higher than 60%, the Ea of the process in synthetic air increases dramatically, indicating that the presence of oxygen lead to the formation of oxidation products is difficult to decompose. The BO produced in fast pyrolysis plant (PPR) acquired by the company Bioware presents chemical composition compatible with the formula CH1,48O0,39N0,008. This result shows a reduction in the percentage of oxygen, a fact that enhances the characteristics of BO for use as fuel. The calorific value is increased the production of BO 15,9 MJ/kg (BCA) to 20,4 MJ/kg, which confirms the increase of the potential use of bio-oil as fuel. Considering this aspect, to preserve the quality of BO and energetically promote the process, lower oxygen concentrations should be employed in the process of decomposition.